Overview of past studies in milk marketing and consumption in Coast Province - Mullins, G.R. (Kenya Ministry of Livestock Development, 1991)
Reviews past research efforts that have focussed on milk marketing and consumption in Coast Province, Kenya, with particular reference to the marketing systems and the marketing and pricing policies for milk and milk products, and the supply and demand of these commodities; discusses the current problems within the Coast Province dairy market and outlines a plan for research and extension that will accommodate and facilitate the expansion of the dairy market.